Considering the Application of Mediation Characteristics for Optimizing Dispute Resolution in Industrial Relations: a Worthwhile Endeavor? - Dananjaya, Nyoman Satyayudha; Karunian, Alia Yofira; Sudiarawan, Kadek Agus; Shara, Made Cinthya Puspita; Martana, Putu Ade Harriestha (Jurnal Wawasan Yuridika, 2023)
This article aims to discuss further the importance of the characteristics of non-litigationdispute resolution through mediation in resolving industrial relations disputes. Thisresearch is descriptive with a normative research type, using a statutory approachand data collection using literature study, then the data is analyzed qualitatively. Theresults obtained from this research are that each type of dispute resolution has itscharacteristics. One of the main reasons why disputes cannot be resolved througharbitration is limited authority. Apart from that, the lack of information, abilities,and knowledge of the parties regarding conciliation and negotiation is the cause ofthese problems. Therefore, mediation is chosen due to its distinctive characteristicscompared to other non-litigation resolutions, such as the mediator's role in assistingthe parties, the absence of decision-making authority, the mediation process focusingon the future, and fostering the creation of win-win solutions.